2021
DOI: 10.1093/treephys/tpab133
|View full text |Cite
|
Sign up to set email alerts
|

The roles of photochemical and non-photochemical quenching in regulating photosynthesis depend on the phases of fluctuating light conditions

Abstract: The induction and relaxation of photochemistry and non-photochemical quenching (NPQ) are not instantaneous and require time to respond to fluctuating environments. There is a lack of integrated understanding on how photochemistry and NPQ influence photosynthesis in fluctuating environments. We measured the induction and relaxation of chlorophyll a fluorescence and gas exchange in poplar and cotton at varying temperatures under saturating and fluctuating lights. When the light shifted from dark to high, the fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Nonphotochemical chlorophyll uorescence quenching (NPQ) is a process in which excess absorbed light energy is dissipated into heat (Ruban 2016). An experiment found that NPQ increased then remained stable when light shifted from dark to high (Han et al 2022), which showed its meaningfulness. In this study, NPQ of full-light needles was signi cantly (p < 0.05) higher than those under lower light, just like a previous experiment found in other evergreen species (Wyka et al 2007).…”
Section: Dynamics Of Light Affect Plant Photosynthetic Responsesmentioning
confidence: 90%
See 1 more Smart Citation
“…Nonphotochemical chlorophyll uorescence quenching (NPQ) is a process in which excess absorbed light energy is dissipated into heat (Ruban 2016). An experiment found that NPQ increased then remained stable when light shifted from dark to high (Han et al 2022), which showed its meaningfulness. In this study, NPQ of full-light needles was signi cantly (p < 0.05) higher than those under lower light, just like a previous experiment found in other evergreen species (Wyka et al 2007).…”
Section: Dynamics Of Light Affect Plant Photosynthetic Responsesmentioning
confidence: 90%
“…However, light intensity and quality are highly variable in space and time according to the time of day, season, geography, climate, and the position of a leaf within canopy (Murchie and Niyogi 2011; Han et al 2022; Cifuentes and Moreno 2022). At the bottom of a dense canopy, the photosynthetic photon ux density (PPFD) and R:FR (red light: far-red light ratio) can be much lesser than that under full light (Chazdon and Fetcher 1984;Way and Percy 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with other research conducted in Scots pine forests, which also found that mean understorey irradiance did not significantly differ between clear and overcast sky conditions, but that there was less variation in understorey radiation under overcast conditions (Messier & Puttonen, 1995). The duration and intensity of fluctuating light have been found to control enzyme activities, stomatal conductance and non‐photochemical quenching, all potentially reducing the efficiency of photosynthesis (Grieco et al., 2020; Han et al., 2022; Kaiser et al., 2018; Yamori et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Photochemical quenching (qP) and non-photochemical quenching (NPQ) were determined as described by Han et al (2022) and Ruban and Wilson (2021) , respectively. Barrs and Weatherley’s (1962) method was used to measure the relative water content (RWC).…”
Section: Methodsmentioning
confidence: 99%